Implementasi Marketing Public Relations dalam Digitalisasi Layanan Informasi Publik: Studi Kasus pada PT Pertamina (Persero) dan Implikasinya terhadap Kepercayaan Publik - Naila Harmalia Balqis; Kherlin Bunga Safira; Erliana Putri; Bayu Setyayoga Purwidyasmara (Jurnal EMT KITA, 2026)
This study aims to analyze the implementation of Marketing Public Relations (MPR) in the digitalization of public information services and its implications for public trust at PT Pertamina (Persero). This research employs a qualitative approach using a document-based case study design. The data consist of 25 selected documents, including official company reports, PPID Pertamina website content, and credible online media such as Kompas.com and CNBC Indonesia, published between 2020 and 2025. Data were analyzed using thematic analysis through systematic stages of data reduction, coding, categorization, and interpretation. The findings reveal that the implementation of digital public information services is manifested in three key dimensions: information transparency, service responsiveness, and communication interactivity. These dimensions are operationalized through features such as open access to public documents, structured digital information request systems, and two-way communication mechanisms via online platforms. The analysis further indicates that these practices contribute to the formation of digital engagement, which mediates the relationship between digital communication practices and the development of organizational credibility and public trust. Unlike previous studies that predominantly focus on social media as the primary communication channel, this study highlights digital public information services as an integral component of Marketing Public Relations. This study contributes to the literature by positioning public information services not merely as an administrative function, but as a strategic communication instrument in building organization–public relationships. However, the study is limited by its reliance on secondary data and does not directly capture public perceptions.